Irrigation Strategies for Rotational Grazing Pasture in Canterbury, New Zealand, and Impacts on Irrigation Efficiency†. (14th September 2018) - KC, Birendra; Mohssen, Magdy; Chau, Henry; Curtis, Andrew; Cuenca, Richard; Bright, John; Srinivasan, Ms; Safa, Majeed
Abstract: To support irrigation efficiency improvement, it is essential to identify the major limitations to irrigation management. Thirty‐two dairy farmers in Canterbury, New Zealand, were interviewed in order to understand current irrigation strategies on pastoral farms, particularly in relation to grazing rotations and plant available water (PAW). A water balance model, IrriCalc, was used to estimate irrigation and drainage from irrigation strategies obtained from the survey. Current irrigation strategies differ greatly from farm to farm, which depend solely on PAW with no consideration for grazing rotations. During shoulder seasons (Sept–Oct and Mar–Apr) the majority of farmers start irrigation at 50% PAW and stop at 80% PAW. During the peak irrigation season (Nov–Feb) irrigation mostly starts at 70% PAW and stops at 100% PAW, leaving no room for precipitation. Results showed that over 14 irrigation seasons (2001/2002–2014/2015) this irrigation strategy would have produced a range of drainage per irrigation season between 40 and 400 mm, which demonstrates a high potential of optimising current irrigation strategies. Better utilization of rainfall during the irrigation season would minimize irrigation requirements and drainage losses. This would help to address the issues of nutrient losses and relieve the pressure on water resources. © 2018 John Wiley & Sons, Ltd.